Das pastorale Theologieverständnis Alberts des Grossen als Ausdruck dominikanischer Zielsetzungen - Bonanno, Valerio (Studien und Texte zur Geistesgeschichte des Mittelalters, 2026)
"This study explores Albert the Great's understanding of theology, aiming to identify the characteristics and limits of the Albertine theological model. The analysis of selected passages from Albert's Super Sententiarum, Summa Theologiae, and biblical commentaries reveals how he viewed the academic theology (biblical exegesis/systematic theology) and the pastoral activity (preaching/disputing with the heretics) as systematically interconnected. Albert's strategic use of the pastoral tasks model from Titus 1:9 allows us to uncover the multidimensionality of his theology and to present it as deeply connected to the core tasks of the Dominican Order"-- Provided by publisher